Hands-on incident response and digital forensics - Sheward, Mike (BCS Learning & Development, 2018)
In this practical guide, the relationship between incident response and digital forensics is explored and you will learn how to undertake each and balance them to meet the needs of an organisation in the event of an information security incident. Best practice tips and real-life examples are included throughout.